Analisis segmen pasar potensial terhadap pengembangan MI Darul Hikam Kota Batu - Derajat, Lingga Saniman; Khoiriyah, Rosa Nur; Masida, Nyi; Andini, Nofita Putri; Zuhriyah, Indah Aminatuz (Maliki Interdisciplinary Journal, 2024)
Marketing Management in the world of education in this era needs to be needed along with competition between educational institutions which is getting stronger because it is driven by various aspects, both community needs and the unlimited digital world. In the discussion that we will discuss under the title "Analysis of Potential Market Segments for the Development of Ibtidaiyah Madrasahs" we will cover how to analyze potential market segments and their development for Ibtidaiyah Madrasahs, considering that every Ibtidaiyah Madrasah is not capable in every region. Therefore, it is necessary to detail this according to our understanding regarding Potential Market Segments and their Development in Madrasah Ibtidaiyah. Apart from that, it aims to understand and describe what the objectives of marketing are in the world of education, especially at Madrasah Ibtidaiyah as well as the factors that can influence the positive and attractive image of Madrasah Ibtidaiyah.